The Amount of Arabic Language Science Necessary to Understand the Islamic Texts and Derive Legal Provisions - Bensala, Youcef; Ali, Abdul Karim (Online Journal of Research in Islamic Studies, 2019)
The Arabic language may be one of the obstacles facing the researcher of legal texts due to the breadth of its vocabulary and the diversity of its structures, formulas and semantics. Moreover, its old age, foreign influence, limited environments of pure Arabic and lack of practice in its pure form even in Arab countries where it is often relegated to academic or religious settings have weakened people’s mastery of Arabic. Allah decided to reveal His Book in Arabic, and chose Muhammad (PBUH) from the pure-tongued tribe of Quraish as His Prophet. As such, the researcher of Islamic texts, should, in principle, have reached mastery of Arabic similar to the language spoken by the Prophet (PBUH) and his companions. The righteous successors and Muslim scholars (Arab and non-Arab) have sought to preserve the purity of the Arabic language. The problem that arises is the role Arabic plays in deriving laws from Islam’s legal texts, and what level of Arabic proficiency is required, the correct methodology for its study and its applicability, and the obstacles to applying this approach. We examine the importance of Arabic in understanding Islamic texts, the amount of Arabic to devise Islamic rulings, the best way to study and use it to understanding the legal texts and draw legitimate inferences, in addition to the obstacles to reaching valid inferences.